2011
DOI: 10.1159/000324685
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Prolong the Use of Uncuffed Hemodialysis Catheters: Results of a Randomized Trial

Abstract: Background: Use of uncuffed catheters (UCs) in hemodialysis patients is common practice. An antibiotic lock has been recommended to prevent catheter-related bacteremia (CRB), although insufficient data are available about the appropriate antimicrobial agent and dose with prolonged use of UCs. Methods: This open-label randomized study was conducted to compare gentamicin/heparin (group A) and taurolidine/citrate (group B), as catheter-lock solutions, in 119 chronic hemodialysis patients in whom a total of 150 UC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…However, it is proven to significantly reduce risk of Gram-negative infections in patients randomized to receive TCLS. Likewise, a recent study observed similar results [22,23]. …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, it is proven to significantly reduce risk of Gram-negative infections in patients randomized to receive TCLS. Likewise, a recent study observed similar results [22,23]. …”
Section: Discussionsupporting
confidence: 83%
“…Moreover, preliminary observations of patients in whom a subcutaneous dialysis device or intravenous catheter is used for hemodialysis suggest that instillation of taurolidine into the catheter lumens may prevent CRB [6,23,24]. However, other studies have shown that it was associated with a greater need for thrombolysis to maintain catheter patency [11,23]. Thus, a systematic review is needed to account for this controversy.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Filiopoulos V et al, the efficacy of two groups of catheter lock solutions (gentamicin/heparin and taurolidine/citrate) in preventing catheter infection and thrombosis was assessed. Catheter-related bacteremia and thrombosis were seen in similar rates in both groups and catheters could be used for 3 months on the average without any thrombosis (Filiopoulos et al, 2011). Another trial investigated the efficacy of tPA in reducing catheter thrombosis and infection.…”
Section: Thrombosis In Central Venous Cathetermentioning
confidence: 97%
“…[21][22][23][24][25] Since publication of the meta-analyses, 5 observational studies and 6 randomized controlled trials (RCTs) have been conducted. [26][27][28][29][30][31][32][33][34][35][36] Three observational studies that evaluated gentamicin-heparin lock solutions, 1 that used 46.7% trisodium citrate, and 1 that evaluated both a gentamicin-heparin solution and taurolidine-citrate solution all found that the antimicrobial lock solutions were associated with reduced CLABSI rates among hemodialysis patients. [26][27][28][29][30] In an RCT by Power et al 31 that compared 46.7% sodium citrate with 5% heparin lock solutions, the investigators found no difference in the rate of CLABSIs (0.7 cases per 1,000 CDs in each group).…”
Section: Antimicrobial Lock Solutionsmentioning
confidence: 99%